Effect of pier height and support flexibility on seismic response of bridges including poundings. Issue 7 (May 2022) - Yang, Z.; Meng, D.; Chouw, N.
In conventional seismic design, bridges usually are assumed to be fixed to a rigid support. This assumption, however, does not correspond to the reality of bridges with shallow footings since they can rock in strong earthquakes. It has been recognised that several factors significantly affect the response of bridges with rocking footings, including support flexibility, pier height and pounding. Most studies so far have mainly focused on a single factor. This research aims to narrow the knowledge gap by investigating the combined effect of pier height, support condition and earthquake characteristics on bridges with rocking ability. A series of shake table experiments on a single-frame bridge with different pier heights and support conditions under hard, medium and soft soil excitations were carried out. The influence of support flexibility was examined by comparing the response of rocking bridges on rigid support with that on soil support. The result shows that regardless of the flexibility of the support, in the case of no pounding, it is beneficial to take rocking footing into account because the maximum bending moment at the pier support can be reduced. However, when pounding was considered, the combined effect can generate an even larger maximum bending moment than that of the fixed-base bridge.